Distinctive expression signatures of serum microRNAs in ischaemic stroke and transient ischaemic attack patients - Wu, Jia; Fan, Chun-li; Ma, Li-juan; Liu, Ting; Wang, Cheng; Song, Jia-xi; Lv, Qiu-shi; Pan, Hao; Zhang, Chun-ni; Wang, Jun-jun (Thrombosis and Haemostasis, 2017)
Circulating microRNAs (miRNAs) have recently emerged as promising biomarkers for ischaemic stroke (IS). However, the expression patterns of specific miRNAs in transient ischaemic attack (TIA) patients have not been investigated. Their predictive values for the presence of IS and TIA and their relationships to the neurological deficit severity of IS and the subsequent stroke risk after TIA remain unclear exactly. In this study, 754 miRNAs were initially screened by the TaqMan Low Density Array (TLDA) in two pooled serum samples from 50 IS patients and 50 controls. Markedly altered miRNAs were subsequently validated by individual quantitative reverse-transcription PCR (qRT-PCR) assays first in the same cohort of TLDA and further confirmed in another larger cohort including 177 IS, 81 TIA patients and 42 controls. Consequently, TLDA screening showed that 71 miRNAs were up-regulated and 49 miRNAs were down-regulated in IS patients. QRT-PCR validation confirmed that serum levels of miR-23b-3p, miR-29b-3p, miR-181a-5p and miR-21–5p were significantly increased in IS patients. Strikingly, serum levels of miR-23b-3p, miR-29b-3p and miR-181a-5p were also significantly elevated in TIA patients. Furthermore, up-regulated miR-23b-3p, miR-29b-3p and miR-21–5p could clearly differentiate between IS and TIA patients. Logistic regression and receiver-operating characteristic curve analyses demonstrated that these altered miRNAs may function as predictive and discriminative biomarkers for IS and TIA, and their distinctive expression signatures may contribute to assessing neurological deficit severity of IS and subsequent stroke risk after TIA.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: microRNAs; biomarkers; brain ischaemia; stroke; transient ischaemic attack